Comparison of effects of a self management booklet and audiocassette for patients with asthma. Issue 6643 (23rd July 1988) - Jenkinson, D.; Davison, J.; Jones, S.; Hawtin, P.
Abstract : The effects on self management of asthma of a specially prepared book and audiocassette tape with similar contents were observed in a controlled study of 177 patients with asthma in general practice. After a run in period of six months patients were randomly given the book, the tape, both the book and tape, or neither. Patients' knowledge of the use of drugs, perceptions of their disability, skill in using an inhaler, consumption of drugs, consultations with their general practitioners, morbidity (from patients' entries on diary cards), and use of the educational material were measured. Knowledge about the use of drugs was significantly increased in the groups who received the material after three months and persisted after 12 months. Patients who had been given the tape or the book and tape increased their scores of knowledge of drugs more than patients given the book alone. Patients in all groups given the material considered that their disability was reduced. There were no other significant changes. Patients given both the book and the tape preferred the book. Patients with asthma can obtain useful information from such material. The paradoxical result whereby patients learnt more from the tape but preferred the book suggests that a distinction can be made between information that patients need, which may be acquired better from an audiocassette, and information that they want, which may be acquired better from a book.